Surface‐directed molecular assembly of pentacene on aromatic organophosphonate self‐assembled monolayers explored by polarized Raman spectroscopy. (15th August 2016) - Yazji, Sara; Westermeier, Christian; Weinbrenner, Dominik; Sachsenhauser, Matthias; Liao, Kung‐Ching; Noever, Simon; Postorino, Paolo; Schwartz, Jeffrey; Abstreiter, Gerhard; Nickel, Bert; Zardo, Ilaria; Cattani‐Scholz, Anna
Abstract : Organophosphonate self‐assembled monolayers (SAMPs) fabricated on SiO2 surfaces can influence crystallization of vapor‐deposited pentacene and thus can affect device performance of pentacene‐based organic thin film transistors. Polarized Raman spectroscopy is demonstrated to be an effective technique to determine the degree of anisotropy in pentacene thin films deposited on three structurally different, aromatic SAMPs grown on silicon oxide dielectrics. Vibrational characterization of pentacene molecules in these films reveals that the molecular orientation of adjacent crystalline grains is strongly correlated on the SAMP‐modified dielectric surface, which results in enhanced interconnectivity between the crystallite domains, well beyond the size of a single grain. It is found that vibrational coupling interactions, relaxation energies, and grain size boundaries in pentacene thin films vary with the choice of SAMP. This information clearly shows that molecular assembly of pentacene thin films can be modulated by controlling the SAMP‐modified dielectric surface, with potentially beneficial effects on the optimization of electron transfer rates. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Raman spectroscopy is used to probe the degree of anisotropy in pentacene thin films deposited on three structurally different aromatic organophosphonate self‐assembled monolayers.